2006
DOI: 10.1103/physrevb.73.153403
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of phase coherence in quasi-one-dimensional ring crystals

Abstract: A comparison of the single-particle ͑SP͒ dynamics of whisker and ring NbSe 3 crystals provides new insight into the phase transition properties of quasi-one-dimensional charge density wave ͑CDW͒ systems. In the incommensurate CDW phase, SP relaxation triggered by an ultrafast laser pulse reflects the formation of collective states, and reveals the divergence of the relaxation time when approaching a transition temperature. The degree of divergence is less pronounced in rings than in whiskers, suggesting a loss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Crystal topology broke through a new stage of understanding of physical phenomena. 12,14,15 The topological crystals are conceptually different from conventional crystals. A crystal is constructed by the infinite repetition of atoms, as shown in Figure 1 (LEFT).…”
Section: Introductionmentioning
confidence: 99%
“…Crystal topology broke through a new stage of understanding of physical phenomena. 12,14,15 The topological crystals are conceptually different from conventional crystals. A crystal is constructed by the infinite repetition of atoms, as shown in Figure 1 (LEFT).…”
Section: Introductionmentioning
confidence: 99%
“…These features of the crystals are consistent with the results of the previous experiments in which we have observed clear charge density waves and superconductivity in the ring-shaped crystals as well as single crystals. [10][11][12][13][14][15]18 In summary, we demonstrated that the topology-change surgery gives us valuable information in crystals. By cutting off the ring-shaped crystals of TaSe 3 , we found a phenomenological relation between the radius of curvature after the topology change and thickness.…”
mentioning
confidence: 55%
“…[3][4][5] By the discovery of rings, Möbius rings and Hopf links of crystals of transition metal-trichalcogenide compound systems (NbSe 3 , NbS 3 , TaSe 3 , and TaS 3 ), [6][7][8][9] we obtained experimental systems for the interplay between the closed-ring topology and local order parameters. Using the topological crystals, effects of the closed-ring topology on charge density waves [10][11][12][13][14][15][16][17] and superconductivity 18 have been investigated. As well as the ordered phases in electron systems, the crystal orders of the topological crystals have rich problems of the interplay between the global topology.…”
mentioning
confidence: 99%
“…Usually the anomalous T dependence of τ exp is observed in many gapped systems, for example, phaseordered systems showing an energy gap opening in the electron band below the transition temperature T c . It has been found that a wide variety of superconductors [1][2][3][4][5][6][7][8][9][10][11][12][13] and density-wave compounds [14][15][16][17][18][19] show diverging behavior of τ exp near T c , as confirmed by femtosecond time-resolved optical spectroscopy. 1,4,5,[7][8][9][10][11][12][13][14][15][16][17]19 The divergence of τ exp in these gapped systems is believed to result from a recursive energy transfer between electrons and phonons.…”
Section: Introductionmentioning
confidence: 90%